2013
DOI: 10.2478/s11686-013-0178-y
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Demodex species infestation and various types of cancer

Abstract: Tumor-associated immune system cells secrete protease and cytokines that can inhibit the immune response. In particular, T-cell effector functions could be inhibited, potentially causing an increase in parasitic infestations. Demodex species are common inhabitants of normal hair follicles. Humans are the specific host for two species Demodex folliculorum and D. brevis. The aim of this study was to investigate the incidence and infestation of D. folliculorum and D. brevis in patients with cancer. In the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
(17 reference statements)
1
8
0
4
Order By: Relevance
“…In the majority of studies, the infestation rate was higher in older as compared to younger individuals . This was also the case in our study, where the older staff members were significantly more infested than the younger students, while a borderline statistical difference was found among the different age groups, where older participants had a higher prevalence than the younger ones.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the majority of studies, the infestation rate was higher in older as compared to younger individuals . This was also the case in our study, where the older staff members were significantly more infested than the younger students, while a borderline statistical difference was found among the different age groups, where older participants had a higher prevalence than the younger ones.…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, more men were infested with Demodex mites than women, though the differences were not significant. While some studies also showed that Demodex prevalence is higher in men than women, in other studies the prevalence was higher in women or equal among men and women …”
Section: Discussionmentioning
confidence: 87%
“…In the post‐transplant setting, Demodex folliculitis has been reported to mimic GVHD . Other important causes of erythematous or papulopustular rashes in post‐HCT patients include drug eruptions, viral exanthems, steroid‐induced acne, photosensitivity, and phototoxic drug reactions .…”
Section: Discussionmentioning
confidence: 99%
“…In the post-transplant setting, Demodex folliculitis has been reported to mimic GVHD. 2 Other important causes of erythematous or papulopustular rashes in post-HCT patients include drug eruptions, viral exanthems, steroid-induced acne, photosensitivity, and phototoxic drug reactions. 1 Confirming the diagnosis can be challenging as the mite is part of the normal flora and is not always visualized on skin biopsy, as occurred in this case, leading to a delay in diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Ayrıca bazı kanser türlerinde Demodex sp. ile enfestasyon insidansının artabileceğini bildiren çalışmalar mevcuttur (4,5) . Sunduğumuz olgu ile kanser, kemoterapi tedavisi, kronik böbrek yetmezliği, organ transplantasyonu gibi immun sistemi bozan durumların Demodex sp.…”
Section: Introductionunclassified